(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The article proposes the notion of Monster Dramaturgy by establishing a parallel with performative dramaturgy, exploring how both concepts interrelate from a perspective in which the body is the central element of the event. In addition, the monster and the performative tension the definition of meaning and representation. In parallel, the article addresses the figure of the monster and monstrosity in various fields of knowledge, relating them to the practices of dramaturgical creation. Authors such as Erika Fischer-Lichte and Della Pollock are the main interlocutors. The research also analyses the “text-accumulation” procedure, a practice synthesized by the artist Kenia Dias.